Improved DEMATEL methodology for effective safety management decision-making - Yazdi, M. (Elsevier B.V., 2020)
Decision-making is a critical step in safety and risk analysis. Decision-making is conducted according to the different sources of information often elicited from filed matter and subject matter experts. Many team-based decision-making methods are developed to identify hazards, determine intervention actions, and to prioritize the efforts to reduce the risk in given conditions. However, the majority of decision-making methods are based on idealistic assumptions such as risk contributing factor in a complex system and independency between the factors. In reality, there is strong interaction among the risk factors and also among the sources of information used in decision-making procedure. There is a requirement to use a decision-making framework that captures the dependency of the risk factors and the source of information. This is achieved by integrating DEMATEL (decision-making trial and evaluation laboratory) methodology with Best-Worst method (BWM) and Bayesian network (BN). The integration is considered at two different stages in the DEMATEL methodology. Application of the integrated DEMATEL is illustrated by adopting a case study of safety management in the high-tech industry. Â© 2020 Elsevier Ltd